Dissolved Organic Matter and Activities of Extracellular Enzymes in Two Lagoons (South China Sea) Affected by Aquaculture - Ou, Linjian; Li, Jianting; Zhang, Xianyang; Wang, Zhou; Zou, Jian; Lu, Songhui (Frontiers in Marine Science, 2022)
Xincun Lagoon and Li’an Lagoon are typical tropical lagoons containing unique seagrass meadow and mangrove forest ecosystems. However, nutrient pollution from human activities threatens ecosystem health in these areas. A year-long bimonthly survey was carried out to study the bioavailability of organic nutrients through hydrolysis of the extracellular enzymes β-glucosidase (GLU), leucine aminopeptidase (LAP), and alkaline phosphatase (AP) in the two lagoons. The results showed that the nutrient statuses in Xincun Lagoon and Li’an Lagoon were highly variable and enriched with organic nutrients, especially nitrogen. Organic nitrogen and phosphorus were actively recycled in the lagoons through active LAP and AP hydrolysis. The enzyme activities were mostly produced by particulate-associated bacteria and were positively regulated by the existence of organic nutrients. The enzymatic stoichiometry results indicated the importance of dissolved proteins and aminopolysaccharides as sources of both carbon and nitrogen and a potential phosphorus limitation on microbial growth in the lagoons. Our results emphasized the importance of EEAs in the recycling of organic nutrients and the potential influence of enriched organic nutrients on both microorganisms and plants in Xincun Lagoon and Li’an Lagoon.